D’Alger à Damas, des auteurs en mal d’archives ? - Ines Horchani (Amnis)
From Algiers to Damascus, colonization did not have the same effects on post-colonial literary creations. The relationship to the past varied according to the type of colonization (former settler colonialism, former protectorate, or former mandate), according to the time periods (two predominant time periods: the 1980’s and the beginning of the 21stcentury), and according to the personalities and paths of the authors. We are interested in the practices of authors inheriting the history of colonial Algeria (Didier Daeninckx, Taos Amrouche, Assia Djebar, Maïssa Bey, Kamel Daoud), Tunisia (Fadhila Chabbi, Léa-Véra Tahar), Lebanon (Amin Maalouf, Wajdi Mouawad), and Syria (Rabee Jaber). For some, the colonial past is so repressed that it becomes explosive; for others, this past is simply unexplored without being obsessional; yet for others, the colonial past seems overshadowed by more recent events, such as civil war. In any case, marks from the colonial past are tangible and can resemble black holes, scars, rifts, or stratum… We will show that these authors from an Arab world, not yet completely restored from colonization, make quite variable usage of real archives (academic or non-academic) and also resort to the creation of imaginary archives.